Performance of sweet cherry cultivars grafted on Colt rootstock - Csihon, Á.; Bicskei, D. K.; Dremák, P.; Gonda, I. (International Journal of Horticultural Science, 2018)
In this paper growing characteristics and fruit bearing parameters of ‘Lapins’, ‘Kordia’, ‘Sweetheart’ and ‘Regina’ sweet cherry cultivars grafted on vigorous Colt rootstock were evaluated at the University of Debrecen, Pallag Experimental Station. Based on our data five years old trees can be described with homogenous strong growing, but very week yielding (2.1-3.1 kg/tree), as while fruit size varies between 26.2 and 27.2 mm. Producing the examined cultivars on Colt rootstock with high plant density requires higher attention and more interventions (root pruning, sawing the trunk) during the technology.